2021
DOI: 10.1093/mnras/stab1803
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase metallicity gradients of TNG50 star-forming galaxies

Abstract: We present the radial gas-phase, mass-weighted metallicity profiles and gradients of the TNG50 star-forming galaxy population measured at redshifts z = 0–3. We investigate the redshift evolution of gradients and examine relations between gradient (negative) steepness and galaxy properties. We find that TNG50 gradients are predominantly negative at all redshifts, although we observe significant diversity among these negative gradients. We determine that the gradients of all galaxies grow more negative with reds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 167 publications
10
42
1
Order By: Relevance
“…In contrast with Hemler et al (2021) and Ma et al (2017), and to be consistent with our observational data, our gas metallicity gradients are normalized to the R e of each subhalo. An individual inspection to each gradient shows that fitting data out to 2 R e results in reliable fits.…”
Section: Tng50 Simulations From the Illustristng Projectsupporting
confidence: 64%
See 1 more Smart Citation
“…In contrast with Hemler et al (2021) and Ma et al (2017), and to be consistent with our observational data, our gas metallicity gradients are normalized to the R e of each subhalo. An individual inspection to each gradient shows that fitting data out to 2 R e results in reliable fits.…”
Section: Tng50 Simulations From the Illustristng Projectsupporting
confidence: 64%
“…Once our sample is constrained, we estimated gas metallicity gradients as done in Hemler et al (2021) and Ma et al (2017). First, the center of each galaxy is defined as the position of the particle (of any type) at the minimum potential, and we define the origin of the coordinate system in this position.…”
Section: Tng50 Simulations From the Illustristng Projectmentioning
confidence: 99%
“…To analyse this correlation in the KURVS-CDFS sample, in Figure 9 we correlate the intrinsic annuli-based metallicity gradients with the galaxies stellar mass. We also show comparison samples from the SAMI survey at 𝑧 < 0.1 (Poetrodjojo et al 2021), the analytical model of Sharda et al (2021a) and results from the TNG hydrodynamical simulations at redshift snapshots 𝑧 = 0, 1, 2 (Hemler et al 2021). The intrinsic metallicity gradients of the KURVS-CDFS galaxies exhibit a similar correlation to the comparison samples, with flatter (or inverted) metallicity gradients at higher stellar mass.…”
Section: Metallicity Gradientsmentioning
confidence: 70%
“…Recent studies have indicated connections between a galaxies gasphase metallicity gradient and its fundamental properties such as stellar mass and stellar continuum half-light radius (e.g. Hemler et al 2021;Sharda et al 2021a,c,b;Boardman et al 2021;Franchetto et al 2021). To analyse this correlation in the KURVS-CDFS sample, in Figure 9 we correlate the intrinsic annuli-based metallicity gradients with the galaxies stellar mass.…”
Section: Metallicity Gradientsmentioning
confidence: 97%
See 1 more Smart Citation